Clinical and Bacteriological Profiles of Blood Culture Positive Sepsis in Newborns - Shrestha, P; Das, BK; Bhatta, NK; Jha, DK; Das, B; Setia, A; Tiwari, A (Journal of Nepal Paediatric Society, 2009)
Neonatal infections currently cause about 1.6 million deaths annually in developing countries. Sepsis and meningitis is responsible for most of these deaths. This study was undertaken to determine the clinical presentations, bacteriological profiles and antibiotic sensitivity patterns of isolates from blood cultures of neonates admitted in a tertiary care hospital in Eastern Nepal. All blood culture reports (n=103) during January 2006 - February 2007 from newborns admitted in neonatal division at BP Koirala Institute of Health Sciences, Nepal were analyzed and antibiotic sensitivity patterns were studied. The positive blood culture was 20% (103/513). Most (97.1%) of the sepsis was caused by single organism, while polymicrobial aetiology was observed in 2.9% cases. Meningitis was documented in 9(8.7%) cases. Staphylococcus aureus (38.8%) and coagulase negative staphylococcus (CONS) (21.3%) are the commonest isolates in blood culture. Among gram-negative organisms, Klebsiella species (11.6%) and Enterobacter species (9.7%) were the leading cause of neonatal sepsis. Majority of newborns with neonatal sepsis presented with refusal to feeds (42.7%), fever (41.7%) and jaundice (41.7%). Most of the organisms showed sensitivity with amino glycosides (gentamicin and amikacin) and third generation cephalosporins. It is concluded that Staphylococcus aureus, CONS, and Klebsiella species remain the principal organisms causing neonatal sepsis and first line antibiotics like amino glycosides should be first choice of drugs. Key words: Blood culture, neonatal sepsis, antibiotic sensitivity. doi:10.3126/jnps.v27i2.1411 J. Nepal Paediatr. Soc. Vol.27(2) p.64-67